A utilização de distalizadores na correção da classe II de Angle - Julião, Victor Hugo [UNESP] (2010)
The Angle class II malocclusion is characterized by a sagittal relation between the first permanent molars so that the mesiobuccal cusp of the upper molar occludes ahead of the buccal groove of the mandibular molar. With this specific dental relation the nature of the problems may be such dentoalveolar, when the relation between maxilla and mandible are normal, or skeletal, when beyond the dental relation the apical bases of maxilla and mandible are involved. Among the treatment modalities are the orthopedic mandibular advancement, dental extractions, orthognathic surgery and the distalization of the upper molars. The aim of this work is to present a literature review about some methods of distalization of the maxillary molars, that may involve or not the patient's cooperation